TIPOLOGI KERAMIK PADA SITUS CERUK MALA-MALA KECAMATAN KODEOHA KABUPATEN KOLAKA UTARA PROVINSI SULAWESI TENGGARA - Asmauliah Asmauliah; Abdul alim; sandy suseno (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2020)
ABSTRAct The Mala-Mala site is a burial site that has a variety of archeological remains, so far we can still find one of them, namely ceramics. The purpose of this research is to find out the shapes and variants of ceramic forms contained on the Site. This study uses a concept foundation that is the concept of ceramics, ceramic parts, and niche concepts. This research is analytical descriptive by using inductive reasoning, with data collection methods through literature study, field observations, sample selection, and interviews, then the data analysis stage is form analysis and then followed by taxonomic classification methods. The results showed that the results of the analysis of farmen forms container edges, container edges, and container bases, in the form of bowls, plates, and container covers. The analysis of the ceramic form above has shown that there are 10 edges of the container consisting of 8 variants, 7 edges of the container consisting of 5 variants, 22 container bases consisting of 9 variants. Keyword :burial sites; ceramic typology; mala-mala site